Farmers’ Preferences for Modern Information Communication Technologies in Trinidad - Lendel K. Narine; Amy Harder; Grady T. Roberts (Journal of International Agricultural and Extension Education, 2019)
In the island nation of Trinidad, farmers have access to public extension services provided through the Ministry of Agriculture, Land and Fisheries but still struggle to get the information they need in a timely manner. Information Communication Technologies (ICTs) offer opportunities to improve the relationship between Extension and farmers. This study, guided by the Uses and Gratification (U&G) theory, sought to assess Trinidadian farmers’ preferences for mobile ICTs. From a convenience sample of 200 farmers in Trinidad, results showed almost all farmers used text messaging, and most used multimedia messaging and WhatsApp. Farmers were deliberate in their selection of medium for receiving different types of information. Findings suggest two-way ICTs are contextually appropriate for communicating with Trinidadian farmers. This study highlights the importance of understanding the information needs and preferences of farmers to ensure effective extension service delivery. While many ICT mediums are available, communicators must seek to utilize those mediums that are widely accessible and adopted by the target audience. The U&G theory provided an appropriate framework to investigate farmers’ preference for ICTs and allowed a critical discussion on the suitability of ICTs in Trinidad’s extension system.
Keywords: Information Communication Technologies (ICT); preferences; mediums; information; extension